Introducing Open Dialogue as part of the WHO QualityRights Project in South Korea: experiences and opinions from an introductory workshop and 1-year pilot practice - Cho, Sooni; Cho, Yong Hyuk; Noh, Jai Sung; Jeong, Seong Kwon; Kim, Shin Kwon; Kim, Seongsu (Frontiers in Psychology, 2024)
This study explores the subjective experiences of participants in a 5-day Open Dialogue (OD) workshop and a one-year pilot practice, conducted as part of the WHO QualityRights Project in South Korea. Twenty-four participants, selected through purposive sampling, completed surveys immediately after the workshop and one year later. Data were analyzed through both statistical and thematic approaches. A statistically significant decrease in the availability of 'Flexibility and Mobility' was observed across all participants (p = 0.044) and a significant reduction in the availability of 'Tolerance for Uncertainty' (p = 0.04) was noted among participants who engaged in network meetings over the course of one year. Qualitative analysis revealed that participants initially felt ambivalent towards OD due to systemic, cultural, and professional challenges. However, through experiential learning, their ambivalence shifted to hope, fostering solidarity and a more positive outlook for future OD practice. Participants recognized that implementing OD supported human rights, while addressing personal, organizational, and policy challenges. The findings provide important insights for developing OD training and implementation guidelines in South Korea. Recommendations include focusing on experiential learning and selecting mixed-group trainees from catchment area institutions, emphasizing the support of client rights, and considering individual, organizational, and systemic levels for successful implementation. This study represents a new case of OD dissemination through a top-down national research and development project and its integration into the WHO QualityRights service package, suggesting complementary potential between OD and global human rights-based mental health initiatives.